LIFE CYCLE ASSESSMENT OF RICE HUSK-BASED ELECTRICITY GENERATION IN A THERMAL POWER PLANT - Cardoso, Orlando Marcos Quadros; da Costa, Tamíris Pacheco; da Silva, Mateus Guimarães (Seven Editora, 2026)
The present study assessed the carbon footprint of electricity generation from rice husk in a thermal power plant located in São Sepé, Rio Grande do Sul, Brazil. For this purpose, the Life Cycle Assessment (LCA) methodology was applied in accordance with ISO 14040/14044 standards, using the OpenLCA software and the Ecoinvent 3.6 database. The functional unit considered was 1 kWh of electricity produced, covering the stages of rice cultivation and processing, biomass transportation, power plant operation, and ash disposal. The results indicated a carbon footprint of 0.036 kg CO₂ eq/kWh, with emissions associated with biomass and ash transportation accounting for more than 80% of the total. Compared with other energy sources, rice husk-based electricity generation demonstrated better environmental performance than coal and natural gas, standing out as a low-impact renewable alternative. The analysis also revealed that mitigation opportunities are mainly concentrated in transportation logistics and in the local valorization of ashes as an agricultural soil amendment. DOI: https://doi.org/10.56238/sevened2026.008-039